2009
DOI: 10.1177/0267323108098943
|View full text |Cite
|
Sign up to set email alerts
|

Media System, Public Knowledge and Democracy

Abstract: We address the implications of the movement towards entertainment-centred, marketdriven media by comparing what is reported and what the public knows in four countries with different media systems. The different systems are public service (Denmark and Finland), a 'dual' model (United Kingdom) and the market model (United States). The comparison shows that public service television devotes more attention to public affairs and international news, and fosters greater knowledge in these areas, than the market mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
305
0
17

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(333 citation statements)
references
References 15 publications
11
305
0
17
Order By: Relevance
“…Aside from longitudinal studies, several comparative studies argue that the impact of choice and the commercialization of media on news media use and knowledge can be studied by investigating countries with different types of media system and political information environments, and thereby how levels of commercialization influence knowledge gaps Banducci et al, 2016;Curran et al, 2009;Fraile & Iyengar, 2014;Soroka et al, 2013). In addition, several studies investigate how exposure to commercial versus public service news may influence learning and knowledge gaps (Aarts & Semetko, 2003;Shehata et al, 2015;Strömbäck, 2016).…”
Section: Concern 6: Towards Increasing Inequalitiesmentioning
confidence: 99%
“…Aside from longitudinal studies, several comparative studies argue that the impact of choice and the commercialization of media on news media use and knowledge can be studied by investigating countries with different types of media system and political information environments, and thereby how levels of commercialization influence knowledge gaps Banducci et al, 2016;Curran et al, 2009;Fraile & Iyengar, 2014;Soroka et al, 2013). In addition, several studies investigate how exposure to commercial versus public service news may influence learning and knowledge gaps (Aarts & Semetko, 2003;Shehata et al, 2015;Strömbäck, 2016).…”
Section: Concern 6: Towards Increasing Inequalitiesmentioning
confidence: 99%
“…On the other, as most of the citizens do not have direct contact with what happens abroad (Soroka 2003: 8), this endows mass media with a gatekeeping role regarding foreign issues (Hill 2003: 275). In the end, what is published by mass media is the only source of information from which most of the population gets their information about foreign affairs (Puglisi and Snyder 2008: 3), which also explains why, in countries where the media is more concerned about international affairs, the knowledge of the general population is also much higher in this area (Curran et al 2009). …”
Section: The Other Side Of the Coin: Argentinian Public Opinion Pmentioning
confidence: 99%
“…Knowledge will forever govern ignorance, and a people who mean to be their own Governors, must arm themselves with the power which knowledge gives" (Madison, 1822). Yet, studies have shown that the market model of the media is the worst at public knowledge performance, compared to the mixed and public serviced models (Curran, Iyengar, Brink Lund, & Salovaara-Moring, 2009;Aalberg, Aelst, & Curran, 2010), consequently reducing democratic freedom of expression, based on knowing truths of public interest that promote genuine personal autonomy and private and public accountability (Restrepo, 2013).…”
Section: Review Of European Studiesmentioning
confidence: 99%